Analysis of 28 Chinese Cases of Bilateral Nevus of Ota and Therapeutic Results With the Q-Switched Alexandrite Laser. Issue 2 (February 2016) - Yang, Jing; Luo, Gaoping; Tuyana, Sanusi; Tong, Xiaorong; Tu, Yating; Tao, Juan
Abstract : BACKGROUND: Nevus of Ota is a dermal melanocytic lesion that presents as bluish hyperpigmentation along the first or second branch of the trigeminal nerve. It is common in Asians. However, bilateral involvement is rare. There has been no detailed report on bilateral involvement in Chinese people. OBJECTIVE: To analyze the clinical data on bilateral nevus of Ota in Chinese patients and determine the efficacy of pulsed q-switched alexandrite laser treatment. METHODS: Twenty-eight cases of bilateral nevus of Ota were diagnosed by clinical appearance, and detailed clinical data were collected. A q-switched alexandrite laser was used for treatment. RESULTS: The incidence of bilateral nevus of Ota was 1.4% (28 of 1985). More than 3 regions were involved in most patients (96.4%), and symmetrical lesions were observed in approximately 60% of cases (17 of 28). The lesion was seen at or soon after birth in 15 patients (53.6%); two-thirds of these patients (10 of 15) had ocular or mucosal involvement. The therapeutic results were excellent or good in 17 cases; the group that received more than 3 treatments and age of starting treatment being less than 6 years had better therapeutic results. CONCLUSION: The pulsed q-switched alexandrite laser is an effective treatment, and earlier intervention with more sessions achieves better results.